Discourse and emotions in international relations - Koschut, S; Hall, T; Wolf, R; Solomon, T; Hutchison, E; Bleiker, R (Oxford University Press, 2017)
The field of International Relations (IR) has recently witnessed the emergence of a wide variety of different approaches to make sense of the many ways emotions work in and through discourse. This forum takes stock of and investigates this link based on two interrelated questions: Why study emotions through discourse? How can we study emotions through discourse? Concerning the first question, we argue that textual and verbal utterances provide us with a promising way to make emotions empirically accessible for researchers. Regarding the second question, we argue that it is essential to develop specific criteria for the study of emotions via speech acts. We propose three criteria that the study of emotion discourse must answer to, which revolve around theory (what is an emotion?), expression (how are emotions communicated?), and effects (what do emotions do?). In a step toward fostering engagement and dialogue on these questions, the contributors of this forum propose a variety of approaches to study emotion discourse in world politics. The idea is to explore the ways in which discourse evokes, reveals, and engages emotions and how these effects can speak to larger questions in IR. Precisely, the goal with this forum is to go beyond the “emotions matter” approach of the first wave of emotions scholarship in IR to offer more specific ways to integrate the consideration of emotion into existing research, particularly that of a constructivist vein.